Numerical simulation of plasma-based raman amplification of laser pulses to petawatt powers - Trines, R; Fiuza, F; Fonseca, R; Silva, L; Bingham, R; Cairns, R; Norreys, P (2011)
Contemporary high-power laser systems make use of solid-state laser technology to reach petawatt pulse powers. The breakdown threshold for optical components in these systems, however, demands beam diameters up to 1 m. Raman amplification of laser beams promises a breakthrough by the use of much smaller amplifying media, i.e., millimeter-diameter-wide plasmas. Through the first large-scale multidimensional particle-in-cell simulations of this process, we have identified the parameter regime where multipetawatt peak laser powers can be reached, while the influence of damaging laser-plasma instabilities is only minor. Snapshots of the probe laser pulse being amplified, generated using state-of-the-art visualization techniques, are presented. © 2006 IEEE.